2017
DOI: 10.1016/j.biopsycho.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

EEG differences between eyes-closed and eyes-open resting remain in healthy ageing

Abstract: In young adults and children, the eyes-closed (EC) resting state is one of low EEG arousal, with the change to eyes-open (EO) primarily involving an increase in arousal. We used this arousal perspective to interpret EC/EO differences in healthy young and older adults. EEG was recorded from 20 young (M=20.4years) and 20 gender-matched older (M=68.2years) right-handed adults during two 3min resting conditions; EC then EO. Older participants displayed less delta and theta, some reduction in alpha, and increased b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
149
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(184 citation statements)
references
References 67 publications
34
149
1
Order By: Relevance
“…Duffy, Albert, McAnulty, & Garvey (1984) observed a weak negative correlation between chronological age and alpha (8-11.75 Hz) amplitude in 30-80-year-old males (r = -0.27). Barry & De Blasio (2017) reported reduced delta (0.5-3.5 Hz), theta (4-7.5 Hz) and alpha (8-13 Hz) power, and increased beta (13.5-24 Hz) power in older compared to young adults; age-related alpha reductions were mainly evident in the posterior right hemisphere, with a weaker effect than observed in the other frequency bands. Gaál et al (2010) observed reductions of delta and alpha power in older adults.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 93%
“…Duffy, Albert, McAnulty, & Garvey (1984) observed a weak negative correlation between chronological age and alpha (8-11.75 Hz) amplitude in 30-80-year-old males (r = -0.27). Barry & De Blasio (2017) reported reduced delta (0.5-3.5 Hz), theta (4-7.5 Hz) and alpha (8-13 Hz) power, and increased beta (13.5-24 Hz) power in older compared to young adults; age-related alpha reductions were mainly evident in the posterior right hemisphere, with a weaker effect than observed in the other frequency bands. Gaál et al (2010) observed reductions of delta and alpha power in older adults.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 93%
“…Features of interest included absolute power (i.e., summed power in different frequency bands), relative power (i.e., power in a given frequency band divided by the total power) and power ratios (i.e., power in one frequency band divided by another) (Cassani et al, 2018;Moretti et al, 2009). Power values were calculated separately for EEG recorded with participants' eyes open and eyes closed to explore potential differences between these two arousal states (Barry & De Blasio, 2017). A secondary aim was to compare the accuracy of resting state EEG with that of structural MRI in classifying AD and MCI.…”
Section: Introductionmentioning
confidence: 99%
“…Differences between eyes-open and eyesclosed power are likely related to states of vigilance and arousal. For example, opening the eyes during resting-state recording causes global alpha desynchronization (57) and increased skin conductance reflecting heightened arousal (57)(58)(59). In fact, people with ADHD have lower arousal levels compared to controls (60,61), which is one of the most reported theories explaining altered EEG spectral power in ADHD (11,15,(60)(61)(62)(63).…”
Section: Markovska-simoska and Pop-jordanova (32) Reported 68% Accuramentioning
confidence: 99%